George Horace Gallup papers - Gallup, George, 1901-1984.
Drafts and printed and near-print copies of speeches, drafts of books, and Gallup Poll releases. Subjects include American foreign policy, the Vietnam War, and public opinion surveys.
Statistician and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Public opinion polls -- United States; Vietnam War, 1961-1975.; United States -- Foreign relations -- 20th century; Vietnam -- History -- 1945-1975.; Authors; Statisticians